Mouse consomic strains: Exploiting genetic divergence between Mus m. musculus and Mus m. domesticus subspecies - Gregorová, Sona; Divina, Petr; Storchova, Radka; Trachtulec, Zdenek; Fotopulosova, Vladana; Svenson, Karen L.; Donahue, Leah Rae; Paigen, Beverly; Forejt, Jiri (Genome Research, 2008)
Consomic (chromosome substitution) strains (CSs) represent the most recent addition to the mouse genetic resources aimed to geneticaly analyze complex trait loci (QTLs). In this study, we report the development of a set of 28 mouse intersubspecific CSs. In each CS, we replaced a single chromosome of the C57BL/6J (B6) inbred strain (mostly Mus m. domesticus) with its homolog from the PWD/Ph inbred strain of the Mus m. musculus subspecies. These two progenitor subspecies diverged less than 1 million years ago and accumulated a large number of genetic differences that constitute a rich resource of genetic variation for QTL analyses. Altogether, the 18 consomic, nine subconsomic, and one conplastic strain covered all 19 autosomes, X and Y sex chromosomes, and mitochondrial DNA. Most CSs had significantly lower reproductive fitness compared with the progenitor strains. CSs homosomic for chromosomes 10 and 11, and the C57BL/6J-Chr X males, failed to reproduce and were substituted by less affected subconsomics carrying either a proximal, central, or distal part of the respective chromosome. A genome-wide scan of 965 DNA markers revealed 99.87% purity of the B6 genetic background. Thirty-three nonsynonymous substitutions were uncovered in the protein-coding regions of the mitochondrial DNA of the B6.PWD-mt conplastic strain. A pilot-phenotyping experiment project revealed a high number of variations among B6.PWD consomics.